2016
DOI: 10.1007/s00441-016-2554-z
|View full text |Cite
|
Sign up to set email alerts
|

The biology of the ABCA3 lipid transporter in lung health and disease

Abstract: The lipid transporter, ATP binding cassette, class A3 (ABCA3) is a highly conserved multi-membrane spanning protein that plays a critical role in the regulation of pulmonary surfactant homeostasis. Mutations in ABCA3 have been increasingly recognized as one of the causes of inherited pulmonary diseases. These monogenic disorders produce familial lung abnormalities with pathological presentations ranging from neonatal surfactant deficiency-induced respiratory failure to childhood or adult diffuse parenchymal lu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
88
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 93 publications
(97 citation statements)
references
References 118 publications
(199 reference statements)
6
88
0
3
Order By: Relevance
“…2), mAbca3 +/− mice appear to have a reverse effect exhibiting decreased number of LBs (Cheong et al, 2007) while no changes in LB sizes have been reported. Thus, the variation between the two models supports the concept that mutations in the mAbca3 gene modify the severity of lung phenotype in the mAbca3 E 292 V –rNeo + mice, similar to those human ABCA3 mutations that have been considered to play a role as modifier genes by either co-expression with other surfactant component gene mutations such as SFTPC mutations (Bullard and Nogee, 2007; Crossno et al, 2010) or expressed in compound heterozygous state (Bullard et al, 2005; Shulenin et al, 2004; Garmany et al, 2006; Doan et al, 2008; Flamein et al, 2012; Beers and Mulugeta, 2016). …”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…2), mAbca3 +/− mice appear to have a reverse effect exhibiting decreased number of LBs (Cheong et al, 2007) while no changes in LB sizes have been reported. Thus, the variation between the two models supports the concept that mutations in the mAbca3 gene modify the severity of lung phenotype in the mAbca3 E 292 V –rNeo + mice, similar to those human ABCA3 mutations that have been considered to play a role as modifier genes by either co-expression with other surfactant component gene mutations such as SFTPC mutations (Bullard and Nogee, 2007; Crossno et al, 2010) or expressed in compound heterozygous state (Bullard et al, 2005; Shulenin et al, 2004; Garmany et al, 2006; Doan et al, 2008; Flamein et al, 2012; Beers and Mulugeta, 2016). …”
Section: Discussionsupporting
confidence: 67%
“…It has become increasingly evident that there are additional cis - and trans -allelic mutations within ABCA3 gene that can act as disease modifiers (Bullard and Nogee, 2007; Kitazawa et al, 2013; Flamein et al, 2012; Goncalves et al, 2014; Beers and Mulugeta, 2016). Several reports have identified patients suffering from chronic lung disorders (with diagnoses of various types of DPLD including pulmonary fibrosis) that carry compound heterozygous mutations (Bullard et al, 2005; Bullard and Nogee, 2007; Kitazawa et al, 2013; Flamein et al, 2012) or an accompanying SFTPC mutation mutations (Bullard and Nogee, 2007; Crossno et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…3h, Supplementary Figure 3e). Meg3 is a known regulator of epithelial cell differentiation, while Abca3 is a crucial factor in surfactant and lamellar bodies' metabolism 11,12 . Mutations of Abca3 have been associated with interstitial lung disease and progressive respiratory distress syndrome and further, knock-down of Abca3 resulted in abnormal lamellar bodies 13 .…”
Section: Hyperoxia Alters At2 Cells Population In Developing Lungsmentioning
confidence: 99%
“…Interestingly, one and the same type of mutation may cause different courses of disease. In this issue, Beers and Mulugeta (2017) provide a comprehensive and detailed review of ABCA3 biology and the consequences of its dysfunction.…”
Section: Developmentmentioning
confidence: 99%